Volcanic ballistic projectile deposition from a continuously erupting volcano: Yasur Volcano, Vanuatu - Fitzgerald, Rebecca Hanna; Kennedy, Ben M; Gomez, Christopher; Wilson, Thomas M; Simons, Benjamin; Leonard, Graham S; Matoza, Robin S; Jolly, Arthur D; Garaebiti, Esline (Volcanica, 2020)
Volcanic ballistics are the main hazard to life and infrastructure from Strombolian eruptions, which are a tourist drawcard, exposing people to this hazard. Most research to date has been to understand this style of eruption and how ballistics form and travel. However, little focus has been placed on how ballistics are distributed within ballistic fields or the inclusion of this data into hazard and risk assessments. In this study we used a UAV to image the ballistic field, and cameras to record eruptions at Yasur Volcano, Vanuatu from 28 July – 2 August and 17 – 19 October 2016. We present the mapped distributions from the two trips, how the field changes with distance and direction from the vent, and how eruption dynamics influence these changes. Our evidence for directionality results in considerable variation in summit ballistic hazard and is an important consideration for ballistic hazard and risk assessments.